Controllable synthesis of ultra-small metal–organic framework nanocrystals composed of copper(ii) carboxylates. Issue 37 (12th September 2016) - Xu, Xiangxing
Abstract : A general method was developed to synthesize ultra-small monodisperse MOF nanocrystals composed of copper(ii ) ions and carboxylate linkers. Abstract : Controlling the size of metal–organic frameworks (MOFs) down to the nanoscale is of great importance for the optimization of their properties. Chemically synthesized MOF nanoparticles commonly range from tens of nanometers to several microns. Herein, a general two-ligand modulation strategy in an interface reaction system is developed to synthesize a series of ultra-small MOF nanocrystals composed of copper(ii ) ions and carboxylate linkers. The size of these MOF nanocrystals can be tuned within 10 nm by the alkyl chain length, the ligand to metal ion ratio and the reaction time. The ion exchange and self-assembly of the MOF nanocrystals were also investigated. They are well dispersed in nonpolar solvents applicable for spin-coating, suggesting their application potentials in functional thin film devices.